Experimental Validation of Mathematical Models in Swimming - Dabnichki, M.; Lauder, P. (1999)
Swimming action, in particular front crawl arm stroke, presents biomechanicists with series challenges. The two major issues are: - reliability of the collected kinematic data - validity and reliability of the utilised mathematical models. The first issue was well researched over the years and viable practical solutions have been proposed addressing certain difficulties such as water refraction, light conditions, etc. (Lauder et al, 1996&1998). The error in these routines was well assessed and was found that an accuracy of reconstruction of less than 3 mm could be achieved in a three-dimensional reconstruction of a volume of 1.5 m3. Therefore, although presenting the researcher with some considerable difficulties, this issue could be satisfactory resolved with a high degree of certainty. However, the assessment the forces involved in swimming and the optimisation of movement pattern to maximise the generated propulsive force remains an unresolved issue. Many studies have utilised mathematical models to assess these forces based on video data. These models are highly idealised and the degree of precision of their results have never been adequately assessed Dabnichki (1998 a&b) showed that in general the reliability of force estimates is highly questionable and strongly dependent on both the accuracy of kinematic data and more importantly the accuracy of models` assumptions. Aims The aim of the current study was to experimentally obtain the amount of propulsive force exerted by the arm during front crawl stroke by means of direct force measurement and to compare to the estimates provided by well established and commonly used mathematical models in order to assess their validity. Methodology The study was conducted by using a mechanical prosthetic arm specially designed to fully resemble a top swimmer`s arm and it was ensured that the mass of the arm as well as the centres of mass of its segment were matching the real ones. The design of the arm is partially highlighted in Lauder and Dabnichki (1996). The data were collected by using two video cameras set perpendicular to the sagittal and frontal plane respectively. Force and power data were independently collected from specially mounted force transducers and voltmeters. Several elbow flexion angles were experimentally examined in order to validate existing theoretical methods. All data collection was synchronised allowing to reliably compare the obtained data. Results and Discussion The findings of the study show that there is a strong nonlinear relation between the drag force and the driving torque by different elbow flexion. The results also suggest that the model of laminar flow cannot give a conclusive answer to the question what is an optimal pattern of the stroke. Initial comparisons suggest that the reliability of the existing theoretical models is restrained to certain parameters and cannot fully account for the pattern of movement as well as arm configuration.